Small is Beautiful...or Not? - Verhagen, Nol (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
This paper explores recent developments within library organisations and their impact for the functioning of university libraries, and more specific, the relations between the central library and decentral libraries. Examples are taken from the University of Amsterdam, the author’s home institution, and from the UKB, the consortium of Dutch Research libraries.